Towards quantifying human experience in the built environment: A crowdsourcing based experiment to identify influential architectural design features. (November 2018) - Ergan, Semiha; Shi, Zhuoya; Yu, Xinran
Abstract: One of the main challenges in the quantification of the influence of architectural design features on human experience is to define the set of architectural design features that people notice immediately in a space as well as to define the type of influence these design features can have on people. Through a crowdsourced experiment, this study provides evidences on the architectural design features that people notice immediately in a space, preferences of people on the spaces configured with these features, and the influence level of these features on overall experience in spaces. Statistical analysis on around 400 subjects' data show that certain features such as the openness of space, presence of windows and daylighting, flexibility in isolation/socialization, level of artificial lighting, density of spaces, and color of surfaces are easy to notice by people and are also powerful to change the human experience. The findings provide an ordering of the identified design features based on their noticeability and influence levels for practitioners to consider in their design decisions. Findings also establish the basis towards objectively quantifying the impact of architectural design features on human experience in spaces. Highlights: Architectural design features are powerful to change the human experience. Nature view/light, accessibility, and openness provides positive experience. A subset of semantic bipolar scales is developed for 18 design features. Crowdsourced results showed that noticeable design features are intuitive to people.